Variability in the Composition of Lavandula angustifolia Extracts due to Extraction Methods. Issue 2 (2nd April 2016) - Babu, G. D. Kiran; Thakur, Vipan; Singh, Bikram
ABSTRACT: Quantitative and qualitative variations of volatiles from Lavandula angustifolia produced by supercritical CO2 extraction (SCE) and by hydro-distillation (HD) were studied. HD produced higher oil yields (2.5%) than the SCE (0.6-1.8%). The yield increased with increase in supercritical CO2 density. Hydro-distilled oil had higher concentration of artifacts due to conditions prevailing in the distillation flask, while SCE produced better-quality extracts in terms of higher concentration of linalyl acetate (44.1–59.8%) and β-caryophyllene (6.3–7.3%) than the HD. The variations in aroma constituents of SCE and HD may be due to variability in solvating power of CO2 and other thermophysical properties of the solvent and/or the solute. For optimum extract yield and quality, the dry spikes may be extracted by SCE at 12 MPa and 35–45°C.